ИДИОСТИЛЬ ЛОНГА: ЛИНГВОСТИЛИСТИЧЕСКИЙ И КОНЦЕПТУАЛЬНЫЙ АНАЛИЗ ДРЕВНЕГРЕЧЕСКОГО РОМАНА - Chakal (Makar), Inesa (Casa Cărţii de Ştiinţă, 2015)
The article is dedicated to the complex research of the idiostyle of the ancient greek writer of the end of the 2nd century A.D. Longus, the author of the novel „Daphnis and Chloe”. On the basis of the writer’s language vocabulary lexical microsystems (lexical-grammatic class, lexical-semantic group, conceptually thematic field, conceptually thematic group) as index of the writer’s idiostyle were described. The connection between writer’s lexical idiosystem and conceptual structure of fiction text was grounded. On the basis of selection of conceptually thematic fields („Nature”, „Shepherd life”, „Love”) in lexical idiosystem it was succeeded to find out the features of functioning of dominant lexemes, which provide basic content-factual information of work, and also take part in creation of tropes (metaphors, epithets, simili etc.), which depend not only on the theme, genre and subject of Longus’s novel „Daphnis and Chloe” but also represent individual stylistic tastes of author.
LONGUS’S IDIOSTYLE: LINGUO-STYLISTIC AND CONCEPTUAL ANALYSIS OF THE ANCIENT GREEK NOVEL
Keywords: идиостиль; лексическая доминанта; лексико-семантическая группа; концепт; Лонг; Longus; idiostyle; CONCEPTUAL ANALYSIS